The effect of palm oil fuel ash (POFA) as cement replacement on high performance concrete (HPC) - Nurhassikin , Sulaiman (2013)
Palm Oil Fuel Ash (POFA) is a by-product of the burning of fiber and shell which are used, as fuel to generate steam and energy required for the operation of mill. It has been used as partial cement replacement for normal concrete, high strength concrete, high performance concrete and aerated concrete. For this research, the effectiveness of POFA as a partial cement replacement in High Performance Concrete (HPC) in term of strength, water absorption and corrosion resistance was investigated. HPC is replaced by weight with 10%, 20% and 30% of POFA. For compression and water absorption testing, a cube sample with dimension 150mm X 150mm X 150mm is used whereas for the corrosion resistance test, the specimen is prepared in a cylinder form with diameter of 80mm and 160mm in height. The specimens are cure using water curing for 7, 28 and 90 days. From the testing carried out, it is found that the compressive strength of UPC with 20% of POFA achieve the highest compressive strength compared to other mix. For the water absorption test, the results shows that UPC with 20% of POFA have a lowest percentage of water absorption compared to other mix. The Half-cell potential results for corrosion also show the same outcome as compressive and water absorption test which is POFA with 20% have a lowest corrosion reading compared to other mix. As a conclusion, it is found that replacement of POFA will enhance the strength and durability of HPC with optimum replacement is 20%.